Chronic kidney disease increases the risks of age-related macular degeneration: a systematic review and meta-analysis - Lin, Ting-Han; Lin, You-Yen; Huang, Yu-Te; Huang, Yu-Chuen; Tien, Peng-Tai; Wan, Lei; Lin, Hui-Ju (Frontiers in Medicine, 2025)
ImportanceAge-related macular degeneration (AMD) and chronic kidney disease (CKD) are common causes of morbidity, with systemic risk factors shared. Clarifying the association between the two is crucial to guiding comprehensive management.ObjectiveThis study aimed to systematically review current and latest evidence on the influence of CKD on AMD prevalence. An investigation was performed into various AMD stages and how different CKD severities exert their effects.Data sourcesDatabases of PubMed and Embase were searched from their inception to 11 November 2024. Reference lists of studies were reviewed, and relevant researchers were contacted. The study was accepted and registered with PROSPERO (CRD420250612669).Study selectionEligible studies of the current review are observational, peer-reviewed, and include quantitative comparisons of AMD prevalence between populations with and without CKD. Studies with overlapping data or investigating AMD incidence were excluded. Twenty studies met the inclusion criteria from the 3,218 initially identified.Data extraction and synthesisWe extracted data and assessed study quality using the Appraisal tool for Cross-Sectional Studies (AXIS) tool for cross-sectional studies. Our meta-analyses followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and were conducted with Review Manager 5.4.1. Risk of bias was evaluated using the AXIS quality appraisal tool, and the overall certainty of evidence was qualitatively assessed following the GRADE approach.Main outcomes and measuresPrimary outcomes are the prevalence of all-stage, early-stage, and late-stage AMD among CKD and non-CKD patients. Secondary outcomes investigated AMD prevalence among patients with different CKD stages. We reported in our analyses the risk ratios (RRs) with 95% confidence intervals (CIs).ResultsAll-stage AMD prevalence was found to be higher among CKD patients (RR: 1.65; 95% CI: 1.49–1.83). Similarly, early-stage AMD was more prevalent among CKD patients (RR: 1.47; 95% CI: 1.26–1.71). In late-stage AMD, an even stronger association was shown (RR: 3.72; 95% CI: 2.14–6.45). Meanwhile, there was no significant difference in AMD prevalence between moderate and advanced CKD stages (RR: 1.08; 95% CI: 0.48–2.46).Conclusion and relevanceOur findings indicate that CKD is significantly associated with higher AMD prevalence. These findings suggest the effects of shared systemic mechanisms and underscore the need for ophthalmic screening in CKD patients. Further studies are needed to strengthen causality and expand generalizability beyond the Asian population.Systematic review registrationThe systematic review was registered in PROSPERO (CRD420250612669).